Separative and Conjunctive Errors: A Note on a New Reading of 4Q99 23 - Martone, Corrado (Henoch, 2020)
This short note deals with a new reading of 4Q99 23 in which Job 36:20 is found. This verse is a crux of the biblical text and the fact of finding it in a pre-Christian manuscript offers the possibility of some observations on the transmission of the text, and on the concept of separative and conjunctive errors.